Transparency in competitive tendering: The dominancy of bounded rationality - Hamisi K. Sama (Cogent Business & Management, 2022)
In an era of intense false impressions, cognitive limitations and imperfect information, where critical challenge is the management of procedural relationships among public procurement partners, it is essential to exploit and identify sources associated with decreasing transparency in competitive tendering. The paper is supported by quantitative approach, using structured questionnaire as a data collection technique in a cross-sectional design. In this study, respondents were public procurement practitioners from Local Governments of Singida and Dodoma Regions in Tanzania, while descriptive statistics, regression analysis and moderated regression analysis were employed to analyse data. From the study results, it can be observed bounded rationality as an important element in explaining the existence of false impressions, cognitive limitations and imperfect information to governing rules and regulations which open possibilities for malpractices and non-compliances in competitive tendering. This paper offers new insights relatively into the nature, size and dominancy of bounded rationality in transparency in translating dominancy of false impressions, cognitive limitations and imperfect information to accountability, integrity and value for money. It fills practical and theoretical gap on nature and source of bounded rationality outcomes and clarifies under which circumstances professionalism, legal infrastructures, information disclosure and trust can be distorted.
Keywords: 650; bounded rationality; competitive tendering; public procurement; transparency